2018
DOI: 10.18280/ijht.360241
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of solar air heater equipped with louvered fins

Abstract: The current work deals with the thermal performance of louvered finned solar air collector. The study involves evaluating various parameters such as temperature rise, thermal efficiency, effective efficiency and insolation compared to that of plane solar air heater. It is observed that at minimum duct height and minimum fin spacing the thermal efficiency shows a noticeable enhancement but the effective efficiency reduced at higher mass flow rate, even may be less than plane solar air heater. This is because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The thermal efficiency increased from 38.6% to 75.5% using fins with a fin length of 10 cm, and the space between two consecutive staggered rows was 2.5 cm. Similar results were found by [52][53][54] that the thermal performance was enhanced by decreasing fin spacing. Bahrehmand and Ameri [55] found that tin metal sheet (TMS) with fins had higher energy and exergy efficiency at a low channel depth compared to collector with fins and without TMS.…”
Section: Absorber With Fins/ribssupporting
confidence: 86%
See 1 more Smart Citation
“…The thermal efficiency increased from 38.6% to 75.5% using fins with a fin length of 10 cm, and the space between two consecutive staggered rows was 2.5 cm. Similar results were found by [52][53][54] that the thermal performance was enhanced by decreasing fin spacing. Bahrehmand and Ameri [55] found that tin metal sheet (TMS) with fins had higher energy and exergy efficiency at a low channel depth compared to collector with fins and without TMS.…”
Section: Absorber With Fins/ribssupporting
confidence: 86%
“…It was observed that the mass flow rate should not exceed 0.05 kg/s since the pressure drop dominates the positive effect of increased thermal efficiency at high mass flow rates. Chand and Chand [52] found that the thermal efficiency and outlet air temperature were enhanced by decreasing louvered fin spacing. Effective efficiency was raised up to an optimum mass flow rate.…”
Section: Geometry Of Fins/ribsmentioning
confidence: 99%
“…Alternatively, increasing the thickness of insulation had no significant effect on the exergy efficiency. Chand and Chand [3] investigated a thermal performance of LFSAH. The study revealed that the thermal performance of LFSAH shows a noticeable enhancement with minimum fin spacing and fin height.…”
Section: Introductionmentioning
confidence: 99%
“…Because at a temperature of t 1 =80°C, an increase in t 2 to 55°C (during the period of a constant drying rate) occurs up to 90 ° C (at the end of the drying process, η will decrease from 0.41 to 0.25), which is 39%. [16][17][18][19][20][21] The efficiency of the solar air heater the efficiency of a solar air heater is determined using the following formula:…”
mentioning
confidence: 99%